BECOMING A PARENT RELATIONSHIP AS ONE OF THE MOST IMPORTANT AREAS OF PERSONAL DEVELOPMENT - Victoria Alexandrovna Kalashnikova (Вестник Северо-Кавказского федерального университета)
In this article the author reveals the urgent problem of the formation of «Parenthood» and the willing- ness to accept such as awareness and acceptance of the «Parenthood» is the basis for the formation and iden- tity of the child in the course of his life.